2016
DOI: 10.3390/pharmacy4040038
|View full text |Cite
|
Sign up to set email alerts
|

Medication Safety: Experiential Learning for Pharmacy Students and Staff in a Hospital Setting

Abstract: Medication Safety has been an established pharmacy specialty in Australian hospitals since the early 2000s and is now one of the ten Australian hospital accreditation standards. Although advances have occurred, medication-related patient harm has not been eradicated. Victorian undergraduate pharmacy programs include some aspects of medication safety, however clinical pharmacy experience, along with interpersonal and project management skills, are required to prepare pharmacists to be confident medication safet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Some evidence from a study comparing an educational game activity with an e-module on increasing the medication safety knowledge showed that both approaches reflected equivalent learning among the students [ 73 ]. Unlike the previous evidence, another study showed that integration of medication safety within educational tools for experiential teaching contributes to improved patient care [ 74 ]. Similarly, the Pharmacy Game involves various elements on medication safety.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence from a study comparing an educational game activity with an e-module on increasing the medication safety knowledge showed that both approaches reflected equivalent learning among the students [ 73 ]. Unlike the previous evidence, another study showed that integration of medication safety within educational tools for experiential teaching contributes to improved patient care [ 74 ]. Similarly, the Pharmacy Game involves various elements on medication safety.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that receiving education on patient safety is associated with improved medical students' patient safety knowledge, skills, and attitude [3][4][5][6][7][8][9][10]. In addition, systematic reviews of published articles have found that many medical schools have adopted a wide range of educational methods to promote patient and medication safety [11,12].…”
Section: Introductionmentioning
confidence: 99%